Pengenalan Abjad pada Anak Usia Dini Melalui Media Kartu Huruf - Ratna Pangastuti; Siti Farida Hanum (Universitas Al-Hikmah Indonesia, 2017)
This study aims to examine factors that affect a child's ability to recognize letters of the alphabet and distinguish several letters that have similar sounds and shape. By using alphabetical card (flashcard) researchers want to improve the ability of objects in recognizing and distinguish letters. This research uses a qualitative descriptive approach with case study research in action research design. Data collection techniques through observation, interviews, and documentation. Semi-structured interview used by researchers to obtain the completeness of the data and find out the problem in detail. The results obtained that the development of the alphabetical is increasing because of stimulus with a alphabetical card. With a child's card game it becomes more fun to recognize the alphabets and can directly play with the alphabetical card directly. In addition to recognizing the alphabets, with a child's alphabetical card can also explore his knowledge through the pictures, colors and shapes that existed in the letters. It indicates that subject has achieved good results in recognizing the alphabet, since from the beginning he has not been able to distinguish the present letters than subject can distinguish letters of similar shape. In addition, subject also able to know the initial letter of a word and can read it.